Exploring Motivation of Learning Anatomy and Its Role in Academic Performance among Preclinical Medical Students in Bangladesh - Sharmista Bhattacharjee; Pragwa Permita Chakraborty (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Anatomy is a building block in medical education. High motivation is required to handle huge amount of information learnt and to achieve academic success. Motivation is often ignored on the belief that medical students are inherently motivated. The aim of this study is to determine the correlation between motivation in learning anatomy and academic performance. Materials and methods: This was a cross sectional study. 192 medical students of 1st and 2nd year from two medical colleges in Bangladesh were included during the period January to June 2025. Data were collected though questionnaire and analyzed on SPSS. Means were compared using unpaired t-test and ANOVA. Pearson’s correlation coefficients were calculated. Results: All subscale and overall motivation scores were found to be satisfactory. Female students (p=0.00) those living at home (p=0.00) non-government medical students (p=0.00) students who studied for longer hours (p=0.00) and those whose mothers had higher education (p=0.01) exhibited significantly higher motivation. Academic scores were positively correlated with task value (r=0.41, p=0.00) intrinsic goal orientation (r=0.35, p=0.00) self-efficacy for learning and performance (r=0.23, p=0.03) and overall motivation (r=0.26, p=0.01) while showing a negative correlation with test anxiety (p=0.02). Conclusion: The results may help educators understand and boost students' motivation and academic success in anatomy. Chatt Maa Shi Hosp Med Coll J; Vol.25 (1); January 2026; Page 25-30